In Silico evaluation of pharmacokinetic parameters of natural bioactives in the oil of Olea europaea L. for possible applications in skin infections - Rossato, Aline; de Souza Filho, Walter Paixão; Martins, Mirkos; da Silva Fernandes, Liana; Rorato Sagrillo, Michele (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Olive oil (Olea europaea L.) contains many useful substances that positively affect human health; they are called bioactive compounds and include phenolic compounds with high antioxidant potential, a-tocopherols (vitamin E), triglycerides, sterols and essential fatty acids such as oleic and linoleic acids. Its molecules give the oil several beneficial health effects due to its antihypertensive, antidiabetic, anticancer, antiatherosclerotic and anti-inflammatory activities. The discovery of new medicines, such as those from medicinal plants, is a more complex problem than it was in the past. The problem is the complexity of the molecules of medicinal plants. In this context, in silico studies, which use computer systems that store, manipulate and display chemical structures and the information associated with them, have become an important tool and increasingly used in research. Based on this, this work sought to evaluate the biological and toxicological parameters of the main natural bioactives of olive oil (oleic and linoleic acid) through the study of in silico predictions, with computational tools (Pass online, Molinspiration , pkCSM and ProTox-II ) and discover the best points of interaction between the compounds with proteins that form bacterial biofilms, through molecular docking. Although this is a preliminary study, which requires further clinical trials and evidence, the results obtained in the study showed that the major fatty acids present in olive oil can be strong candidates to be used in biological applications because in prediction studies computational and molecular docking, proved to be biologically safe, with good pharmacological properties and with good ligand-protein interactions.